(untitled) - Miner, Earl (Stanford, CA., 1968)
The poetry written by the Japanese imperial court between A.D. 550 and 1350 is regarded as one of the great literatures of the world. This volume introduces readers to that literature, offering at once a condensation, a reorganization, and an extension.
Keywords: Japanese poetry,Japanese poetry; History and criticism,Translations into English